UNCOVERING THE WRITERS PURPOSES: AN ANALYSIS OF THE GOALS OF THE JAKARTA POSTs OPINION ARTICLES TOWARDS THE 2014 LEGISLATIVE ELECTION - Fitri Budi Suryani; Ahmad Hilal Madjdi (Soegijapranata Catholic University, 2014)
During the open campaign of the 2014 Indonesian legislative election, the way how the writers of opinion articles in newspapers perform their writing in relation with the context of the campaign is an interesting phenomenon as the fact that people writing about social matters are inevitably influenced by the way they perceived them, as well as their choice of topics and the way they approach them, by their own social experiences and values and political commitments (Fairclough, 1992). This study is aimed at revealing the short term goals and long term goals of the opinion articles in The Jakarta Post towards 2014 Indonesian legislative election. The data were collected from sixteen opinion articles in The Jakarta Post during the open campaign. The result indicates that the number of articles with unparallel purpose is higher than that of articles with parallel purpose.